Penerapan Metode Content Management System Untuk Mempermudah Mengubah Tampilan Website - Yohanes Setiawan; Silvia Rostianingsih; Indro Setiawan (Jurnal Infra, 2019)
Advances in science and technology bring new problems and challenges. One of them is the need to change the appearance of the website quickly and easily. The problem is that there are still many website owners who are not familiar with coding so changing the display is quite time consuming and difficult. In this study an experiment was conducted by categorizing each part of the website. each part is given a variable that can read input from the user and enter it into the database. the system then reads the database and changes its appearance to the data in the database. The test results show that the method of reading variables and databases can change the appearance of the website. website appearance can be changed without having to change the code in it.